Post-Conflict Peace Education to Build Sustainable Positive Peace in Aceh - Suadi Zainal (Proceedings of AICS - Social Sciences, 2016)
This study aims to analyze the post-conflict peace education model developed by the Aceh Government to realize a peace culture as the efforts to establish sustainable positive peace in Aceh. Many experts believe that peace education is able to reduce or even eliminate the violence and foster a peace culture. For this instance, Aceh had implemented peace education which initiated by UNICEF during the conflict. Many senior high schools in Aceh region had been assisted by UNICEF to implement peace education by providing training to the teachers. After the conflict period the same thing also has been implemented by the Department of Culture and Tourism of Aceh Government. However, this study found that the implementation of peace education at schools has not implemented in accordance with the concepts of peace education developed by peace experts and international organizations such as UNESCO. Therefore, this study will analyze the peace education developed in Aceh to build sustainable positive peace.